2010
DOI: 10.1088/0022-3727/43/38/385301
|View full text |Cite
|
Sign up to set email alerts
|

Surface-plasmon voltammetry using a gold grating

Abstract: Using a sensitive optical wavelength modulation technique the surface-plasmon excited on a gold grating surface immersed in sulphuric acid is studied at the same time as cyclic voltammetry is undertaken. Because of the optical sensitivity of the modulation technique significant optical effects are observed at potentials well below those at which any gross oxidation effects occur. PACS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 62 publications
(166 reference statements)
2
11
0
Order By: Relevance
“…As in the case of sulfate, a large cathodic current is present for the protonation of the Au film electrode and HER 50. Just as is the case for sulfate adsorption, clear acetate adsorption and desorption peaks were present while hydrogen-related and secondary reactions were not detectable.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…As in the case of sulfate, a large cathodic current is present for the protonation of the Au film electrode and HER 50. Just as is the case for sulfate adsorption, clear acetate adsorption and desorption peaks were present while hydrogen-related and secondary reactions were not detectable.…”
mentioning
confidence: 80%
“…28-31, 36, 39-44 Also unlike the ITO substrate, anions readily adsorb to gold at anodic potentials [45][46][47] causing large changes in optical and electronic properties of the thin film. [48][49][50] Au nanoparticle monomers and chemically assembled dimers were deposited onto the two substrates, 51 and surface ligands were chemically removed from the monomers and dimers to leave the nanoparticles in electrical contact with the Figure 1. The potential-induced spectral shifts of Au plasmonic nanoparticles in Na 2 SO 4 electrolyte were strongly substrate-dependent.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the combination of EC and surface plasmon resonance (EC-SPR) has become a powerful tool to study the surface chemical reaction process. The process is known as an oxidation–reduction reaction [ 2 , 15 ]. The recent report demonstrated that the optical, dielectric and electrochemical properties on the deposited metal film can be monitored in real time from the EC-SPR detection [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%